Kewajiban dan Hak Negara dengan Warga Negara dalam Demokrasi - Zahra Nauli; Elviana Elviana; Sasmi Nelwati (Lembaga Pengembangan Kinerja Dosen, 2024)
Harmonizing the obligations and rights of the state with citizens in Indonesian democracy is important to achieve a harmonious balance between rights and obligations. The obligations and rights of citizens are regulated in the 1945 Constitution and other statutory regulations. In a democracy, citizens have rights and obligations that must be carried out responsibly. Citizens’ obligations include involvement in the democratic process, self-development and service to the country. Citizens’ rights include human rights and the rights guaranteed in the 1945 Constitution. Harmonization of citizens’ obligations and rights can be achieved through character education and citizens’ awareness of their rights and obligations.